Organic acids and/or compound with defined microorganisms to control Salmonella enterica serovar Enteritidis experimental infection in chickens - Sterzo, EV [UNESP] (2007)
The association of human foodborne salmonellosis with poultry products enhanced the efforts to control Salmonella Enteritidis in poultry farms. Dietary organic acid supplementation is one of the measures currently used to reduce the presence of undesirable microorganisms. Another method to control enteric Salmonella in poultry is competitive exclusion using defined or undefined microorganisms products. Organic acids and microbiological methods to accelerate the development of the intestinal microbiota can be used individually or in combination. The present study evaluated the effect of dietary supplementation of an acidifier and of a defined multi-strain microbial mixture (Biomin® PoultryStar) via drinking water in the control of the intestinal colonization of broilers by Salmonella Enteritidis. Four experiments were performed. The first experiment showed that the organic acids mixture was able to prevent Salmonella Enteritidis colonization of ceca in both inclusion rates applied (p<0.05). In the second and third experiments the probiotic either individually or in combination the acidifier, both in high and low doses reduced the incidence of Salmonella Enteritidis in the cecal contents (p<0.05). In these three experiments, birds were orally challenged. Similar results were obtained in a fourth trial, in which challenge was made by contact.